A Multimodal Analysis to the Construction of Identity in Online Dynamic Platform - Hussein Katea, Haider; Sabeeh Naser, Mutar; Hachim Malih, Jaafar (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents a semiotic analysis to the use of language in combination with nonlinguistic resources for identity construction. This study then, traces the role of those semiotic resources or mode of communication such as (texts, symbols, pictures and colors etc.) in Facebook profiles. Analytically, those modes will be conducted as direct self-representational devices to design and construct identity in online channel. The study explores not only the parallel strategies used in constructing identity, but also to understand how that/those resource(s) work closely together to construct that identity (ies) in online environment. In spite of the fast development of technology and new methods of communication, Facebook was chosen as it permeates our daily culture. Facebook is the most affordable and familiar online means of social communication. In order to achieve the aim(s) of this study, a multimodal analysis is presented set within the theoretical framework of ‘Critical Discourse Analysis’. Based on a quantitative analysis, this exploratory research investigates 120 male and 55 female students University Facebook’s profiles. All of underlying profiles are presented and analyzed in coded profile usernames. Results showed that these devices or semiotic resources were seen as sets of signs or systems combine to emerge semiotic choice as an active performance, by which each users creates meaning and carries cultural value and significance (i.e., identity). Meanwhile, the study also found that most of these profiles (identities) seem pretty much unstable (i.e., flexible) and differ from their real world specially in terms of name, age, sex, nationality. This can be attributed to a mistaken assumption that presenting a real identity could post private and intimate information in real world and then reflect their real identity the matter which may crash with users’ social, political, security and religious traditions and beliefs. Hopefully, these findings can give a better understanding to online identity construction within Iraqi culture.